Beyond the Screen : Transformations of Literary Structures, Interfaces and Genres - Gendolla, Peter; Schäfer, Jörgen (Medienumbrüche, 2015)
While literature in computer-based and networked media has so far been experienced by looking at the computer screen and by using keyboard and mouse, nowadays human-machine interactions are organized by considerably more complex interfaces. Consequently, this book focuses on literary processes in interactive installations, locative narratives and immersive environments, in which active engagement and bodily interaction is required from the reader to perceive the literary text. The contributions from internationally renowned scholars analyze how literary structures, interfaces and genres change, and how transitory aesthetic experiences can be documented, archived and edited.